ARROGANCE (HUBRIS) SYNDROME IN SPORTS; SCALE DEVELOPMENT STUDY - Tutar, Ömer Faruk; Nacar, Eyyup (Munzur Üniversitesi, 2022)
The aim of our research is to develop a scale with proven validity and reliability to measure the Arrogance (Hubris) syndrome levels of athletes participating in sports activities. In the development process of the scale, first of all, an item pool was created by taking the opinions of experts working in the psycho-social fields of sports. Along with the item pool, certain demographic variables were also decided. After getting approval from expert opinions, the draft was tested with a pilot study. Then, data were obtained from active athletes, the main group of the study. The factor loads of the scale, the questions to be eliminated, the level of reliability and the level of explained variance were determined by performing explanatory factor analysis together with the results. As a result of confirmatory factor analysis, the suitability of the goodness of fit indices and the factor structure of the scale; whether a change is required in the scale structure with modification indices and residual value matrices; The validity and reliability of the scale structure were determined by correlational analyzes between the factors, the mean variance extracted, internal consistency tests and composite reliability tests. As a result, the “Arrogance (Hubris) Syndrome Scale” consisting of 12 items and 3 sub-dimensions was developed.

Araştırmamızın amacı sportif etkinliklere katılan sporcuların kibir (hubris) sendromu düzeylerini ölçmek üzere geçerlilik ve güvenirliği kanıtlanmış bir ölçek geliştirmektir. Ölçeğin geliştirilme sürecinde öncelikle sporda psiko-sosyal alanlarında görev yapan uzmanların görüşleri alınarak madde havuzu oluşturulmuştur. Madde havuzu ile beraber belirli demografik değişkenlere de karar verilmiştir. Uzman görüşlerinde onay alındıktan sonra taslak pilot çalışma ile test edilmiştir. Ardından çalışmanın asıl grubu olan aktif sporcular üzerinden veriler alınmıştır. Gelen sonuçlar ile beraber açıklayıcı faktör analizi yapılarak ölçeğin faktör yükleri, elenmesi gerek sorular, güvenirlik düzeyi ve açıklanan varyans düzeyi belirlenmiştir. Doğrulayıcı faktör analizinden sonra, uyum iyiliği indeksinin ve ölçek faktör yapısının uygunluğu; Revizyon indeksleri ve artık değerler matrisi ile ölçeğin yapısında değişikliğe ihtiyaç olup olmadığı; Ölçek yapısının geçerlik ve güvenirliği, faktörler arası korelasyon analizi, çıkarılan ortalama varyans, iç tutarlılık testi ve bileşik güvenilirlik testleriyle de ölçek yapısının geçerlilik ve güvenilirliği tespit edilecektir. Sonuç olarak 12 madde 3 alt boyuttan oluşan “Kibir (Hubris) Sendromu Ölçeği“ geliştirilmiştir.
Sporda Kibir (Hubris) Sendromu; Ölçek Geliştirme Çalışması